Novel role for thioredoxin reductase‐2 in mitochondrial redox adaptations to obesogenic diet and exercise in heart and skeletal muscle. (12th June 2013) - Fisher‐Wellman, Kelsey H.; Mattox, Taylor A.; Thayne, Kathleen; Katunga, Lalage A.; La Favor, Justin D.; Neufer, P. Darrell; Hickner, Robert C.; Wingard, Christopher J.; Anderson, Ethan J.
Key points:   For reasons not completely understood, obesogenic high‐fat, high‐sucrose (HFHS) diets and exercise training both increase free fatty acid utilization and chronic oxidative stress, yet the former is deleterious to cardiovascular/metabolic health, whereas the latter is beneficial.   Here, we report that the heart shows decreased mitochondrial H2 O2 (mH2 O2 ) generation following HFHS diet, while skeletal muscle shows increased mH2 O2, and uncover a novel role for thioredoxin reductase‐2 (TxnRd2) underlying these differences.   We also show that TxnRd2 is critical to controlling mH2 O2 levels during mitochondrial fatty acid oxidation, especially following exercise training in skeletal muscle.   These findings are important in that they illustrate how the heart and skeletal muscle have contrasting adaptations in antioxidant capacity in response to HFHS diet, and uncover a new role for TxnRd2 in the overall control of mH2 O2 in these organs with HFHS diet and exercise training. Abstract  Increased fatty acid availability and oxidative stress are physiological consequences of exercise (Ex) and a high‐fat, high‐sugar (HFHS) diet. Despite these similarities, the global effects of Ex are beneficial, whereas HFHS diets are largely deleterious to the cardiovascular system. The reasons for this disparity are multifactorial and incompletely understood. We hypothesized that differences in redox adaptations following HFHS diet in comparison to exercise may underlie this disparity, particularly in mitochondria. Our objective in this study was to determine mechanisms by which heart and skeletal muscle (red gastrocnemius, RG) mitochondria experience differential redox adaptations to 12 weeks of HFHS diet and/or exercise training (Ex) in rats. Surprisingly, both HFHS feeding and Ex led to contrasting effects in heart and RG, in that mitochondrial H2 O2 decreased in heart but increased in RG following both HFHS diet and Ex, in comparison to sedentary animals fed a control diet. These differences were determined to be due largely to increased antioxidant/anti‐inflammatory enzymes in the heart following the HFHS diet, which did not occur in RG. Specifically, upregulation of mitochondrial thioredoxin reductase‐2 occurred with both HFHS and Ex in the heart, but only with Ex in RG, and systematic evaluation of this enzyme revealed that it is critical for suppressing mitochondrial H2 O2 during fatty acid oxidation. These findings are novel and important in that they illustrate the unique ability of the heart to adapt to oxidative stress imposed by HFHS diet, in part through upregulation of thioredoxin reductase‐2. Furthermore, upregulation of thioredoxin reductase‐2 plays a critical role in preserving the mitochondrial redox status in the heart and skeletal muscle with exercise.